PENGARUH KEMAMPUAN GURU MENGGUNAKAN MEDIA BERBASIS KOMPUTER TERHADAP PERHATIAN PESERTA DIDIK DALAM PEMBELAJARAN PAI DI SMPN 2 PINRANG - Aljinnah hj (Al-Ishlah: Jurnal Pendidikan Islam, 2017)
This article discusses the influence of teacher ability using computer-based media to the attention of learners on learning PAI in SMPN 2 Pinrang Regency. This toward study aims to determine the ability of teachers using computer-based media, the attention of learners on learning PAI in SMPN 2 Pinrang regency, and the effect of teacher ability using computer-based media to the attention of learners on learning PAI in SMPN 2 Pinrang regency. This type of research is quantitative research, as it find the objective, valid, and reliable data using numerical data, preferably observation, questionnaires, documentation. Data obtained through observation, questionnaires, and documentation. The results of this study indicate that the ability of teachers using computer-based learning media significantly influence the attention of learners on learning PAI SMPN 2 Pinrang District. Known from the results of hypothesis testing was proposed alternative hypothesis can be accepted. Based on the calculation, r calculated = 1,000 > r table = 0,169 at 5% significant level so it is concluded that ho is rejected and ha is accepted. Means there is a significant positive influence between variables x and y variables. T test results show t arithmetic greater than t table, 6.029>1.985, meaning Ho rejected or Ha accepted. the calculation results obtained by determination coefficient of 0.27,7 means the correlation value of 27.7 percent of independent variables can explain the deviation and dependent variables.Some of the implications in this study as a form of learning process development is the school is expected to facilitate the process of computer-based learning. Availability of infrastructure facilities will maximize the motivation, interest and attention of learners so that achievement and learning outcomes can be maximized.